A antinegritude em O Alegre Canto da Perdiz, de Paulina Chiziane - Lopes, Michelly Cristina Alves (2024)
The author Paulina Chiziane, the first black woman to publish novels in Mozambique and the first African to win the Camões prize (2021), has been standing out in Portuguese-language African literature, mainly because she deals with topics considered taboo in her country – namely: witchcraft, polygamy, racial issues, rape, prostitution, colonization, among others. In this thesis, we chose the novel O alegre canto da perdiz (2008), in which the author collects stories narrated by other women and uses her writing as a way of denouncing the problems faced by women in Mozambique. The objective of this study is to analyze the experience of the black characters in the work who use anti-blackness – a concept coined by João Costa Vargas (2017) from Afropessimism – as a mechanism to resist the oppression imposed on their bodies and minds by colonization. To do this, they absorb eurocentric ideals and put into practice an anti-black experience, thus accepting the narcissistic mirror of the white man with the aim of surviving within this society. Anti-blackness understands that the black/non-black dyad is fundamental to understanding the relationships carried out in the lives of black people. In this sense, the concept differs from racism and will be the primary element for studying Chiziane's work. Regarding theory, among several authors, the studies Fantz Fanon (1952), Homi Bhabha (1994), Achille Mbembe (2018), João Costa Vargas (2017; 2020) and Osmundo Pinho (2020) will be fundamental; to deal with the history of Mozambique Cabaço (2007) and Mindoso (2017); dealing with the post-colonial and Kimberlé Crenshaw (2004) dealing with intersectionality. At the end of this study, it will be possible to verify that when using anti-blackness as a mechanism to survive and resist in that society, the main character fails in all instances, as the system that has this concept as its foundation does not allow the victory of a black woman. Precisely because, as Costa Vargas (2017; 2020) postulates, black people represent the non-human, but they are necessary for humanity to exist as it is